2008
DOI: 10.1002/elan.200804314
|View full text |Cite
|
Sign up to set email alerts
|

A Glucose Biosensor Based on Immobilization of Glucose Oxidase into 3D Macroporous TiO2

Abstract: 3D macroporous TiO 2 inverse opals have been derived from a sol-gel procedure using polystyrene colloidal crystals as templates. EDS and SEM showed a face-centered cubic (FCC) structure TiO 2 inverse opal was obtained. Glucose oxidase (GOx) was successfully immobilized on the surface of indium-tin oxide (ITO) electrode modified by TiO 2 inverse opal (TiO 2(IO) ). Electrochemical properties of GOx/TiO 2(IO) /ITO electrode were characterized by using the three electrodes system. The result of cyclic voltammetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…For the preparation of the host-guest nanostructured composites, the intensification of mass transfer in the pores is very important because it is mainly the ratecontrolling step of the assembly process. Through electrochemical synthesis, low-temperature chemical reaction, sensor technology, layers of electrostatic selfassembly technology, and other physical chemical methods we successfully prepared magnetic composite microspheres, compound semiconductor fluorescent microspheres, flavor prolonged-release composite microspheres and fixed-peroxidase complex [27][28][29][30][31][32][33]. Figure 5 shows the process for the assembly of CdSe nanocrystals (NCs) in the pores of mesoporous silica (MS); the expanding of the pore size and the intensification of the mass transfer in the pores are very important for the assembly process.…”
Section: Confined Assembly and Application Of Nanocompositesmentioning
confidence: 99%
“…For the preparation of the host-guest nanostructured composites, the intensification of mass transfer in the pores is very important because it is mainly the ratecontrolling step of the assembly process. Through electrochemical synthesis, low-temperature chemical reaction, sensor technology, layers of electrostatic selfassembly technology, and other physical chemical methods we successfully prepared magnetic composite microspheres, compound semiconductor fluorescent microspheres, flavor prolonged-release composite microspheres and fixed-peroxidase complex [27][28][29][30][31][32][33]. Figure 5 shows the process for the assembly of CdSe nanocrystals (NCs) in the pores of mesoporous silica (MS); the expanding of the pore size and the intensification of the mass transfer in the pores are very important for the assembly process.…”
Section: Confined Assembly and Application Of Nanocompositesmentioning
confidence: 99%
“…Well aligned TiO 2 nanotube arrays (NTAs) were synthesized by Grimes via anodizing Ti sheets in HF solution [7]. The vertically oriented TiO 2 NTAs became a competing substrate in sensors, including gas sensor [8,9], COD sensor [10,11] and biosensor [12,13], due to the special architecture of nanotube arrays.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 nanotubes have been used to immobilizing proteins and enzymes in biomaterial and biosensor applications because of high sensitivity at the near-infrared (750 nm) and near-ultraviolet (400 nm) wavelengths [19]. It has been demonstrated that the large surface area, good chemical stability and nontoxicity of the TiO 2 have been achieved with dierent nanocomposite and 3D macroporous structures [20,21].…”
Section: Introductionmentioning
confidence: 99%